Mytens tvang - Albinus, Lars (Religionsvidenskabeligt Tidsskrift, 1999)
<p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; line-height: 10.8pt; text-align: justify; mso-line-height-rule: exactly; mso-pagination: widow-orphan; tab-stops: 0cm 14.2pt 28.4pt 42.65pt 56.85pt 71.1pt 85.3pt 99.5pt 113.75pt 127.95pt 142.2pt 156.4pt 170.6pt 184.85pt 199.05pt 213.3pt 227.5pt 241.7pt 255.95pt 270.15pt 284.4pt 298.6pt 312.8pt 327.05pt;">The purpose of the article is to show how the negative dialectics of Adorno gets involved with a concept of myth that is questionable in several respects. First of all, Adorno tries to combine, but rather conflates, two understandings of myth. On the one hand, the concept of myth is defined as the ancient Greek mythos, in which the subject of man is projected on to nature; on the other hand, myth is defined as the backfire of enlightenment, in which self-reflection becomes the blind spot of instrumental reason. Along these lines of argument, Adorno’s interpretation of Homer, which, at any rate, is highly inspiring, attempts to demonstrate that Odysseus is already enlightened in that he keeps the myth at bay in order to gain his self. The point is, as a matter of dialectic necessity, that he just ends up in myth once again, albeit in the second sense, namely by being a victim of his own self-denial. A question that seems to remain unanswered, though, is how the two kinds of myth are related. Further, Adorno draws on a problematic distinction between myth and literature in order to claim that Homer separates himself from the realm of myth. By adopting Adorno’s own game of interpretation, however, it is possible to regard myth as such, including the Homeric one, as being contingently open-ended rather than just a matter of dialectic determination.